Analisis Antropometri dan Biomekanik Penggunaan Mesin Pemetik Daun Teh Tipe GT 120 Ochiai - Andika Herianto Simarmata; Kralawi Sita; Totok Herwanto; Ahmad Thoriq (Jurnal Tanaman Industri dan Penyegar, 2020)
Application of tea harvest mechanization can increase work productivity, cost efficiency, and reduce the amount of starch loss in tea leaves. The problem is that the harvester machines that are operated in most tea plantations in Indonesia are imported. The harvester machine operators have the potential to experience skeletal, muscular, and peripheral nerve disorders called Musculoskeletal Disorders (MSDs). This study aims to evaluate the design of the type GT 120 Ochiai tea leaf harvester machine based on operator anthropometry and to find the operator's working posture during the tea picking process that needs immediate improvement. Anthropometric data were collected through measurements of the operator's body dimensions, while biomechanical data were collected through video recordings of the work-movements of all operators in operating the machine with a land slope of 5o – 10oand a land slope of 35o–40o at a plant height of 75 cm to 110 cm. Data analysis was performed using the REBA (Rapid Entire Body Assessment) and OWAS (Ovako Working Posture Analysis) methods. The results showed that the design of the type GT 120 Ochiai engine was in accordance with the operator's anthropometry. The results of REBA analysis show that there is a high work risk when operating the harvester machine, namely in the land conditions with a slope of 35o – 40o with a plant height above 100 cm and when moving the sacks of the harvest to a temporary shelter. Meanwhile, according to the results of the OWAS analysis, it is necessary to take corrective action as soon as possible, namely the position of operator 3 and operator 4 and it is necessary to change the position of operator 1 and operator 2. Based on the results of the REBA and OWAS analysis, it is better if the operator’s work shift changes in machine operation with the slope of the land 35o – 40o.